Leading innovation in the public sector: Exploring the mediating role of motivation to learn and the moderating role of power distance - Sugandi, Ramdan Fatra; Etikariena, Arum (University of Islam Malang, 2024)
Innovation is crucial for organizations' performance, success, and long-term survival. Despite its importance, studies on factors influencing the emergence of innovative work behavior remain inconsistent. This study, grounded in the Interactionist Perspective of Creativity theory, explores the role of motivation to learn as a mediator and Hofstede's national culture dimension of power distance as a moderator in the relationship between transformational leadership and innovative work behavior. The study sampled 210 public sector employees in Indonesia using convenience sampling. Data were collected through an online self-report survey employing the multifactor leadership questionnaire, the innovative work behavior scale, the motivation to learn scale, and the power distance scale. Analysis of the PROCESS macro for SPSS version 26 revealed that motivation to learn fully mediates the relationship between transformational leadership and innovative work behavior. However, power distance does not moderate this relationship directly or through the motivation to learn. This implies that the desire to learn and innovate remains effective for public sector employees regardless of hierarchical differences. Thus, no matter how authority is structured within the organization, the motivation to learn is crucial for fostering innovation.